2015
DOI: 10.1111/jpm.12227
|View full text |Cite
|
Sign up to set email alerts
|

Supporting recovery from hoarding and squalor: insights from a community case study

Abstract: People with hoarding behaviours acquire a large number of possessions that are often of limited or no monetary value and which they are unable or unwilling to discard. Such behaviours can substantially impair a person's ability to attend to their normal daily activities, cause substantial distress and lead to squalid living conditions. Living in squalor can compromise a person's health and safety, be a public health issue and present substantial challenges to family, carers, social service agencies and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This observation is similar to that of another study wherein it was reported that in 88% of the complaints, unhealthy living conditions were found [6]. For this reason, hoarding cases are considered a public health hazard that compromises the entire surrounding community [5,7,9]. This condition may increase the risk of health problems and zoonotic diseases, such as leptospirosis, gastrointestinal infections, and venomous animal accidents, among others.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This observation is similar to that of another study wherein it was reported that in 88% of the complaints, unhealthy living conditions were found [6]. For this reason, hoarding cases are considered a public health hazard that compromises the entire surrounding community [5,7,9]. This condition may increase the risk of health problems and zoonotic diseases, such as leptospirosis, gastrointestinal infections, and venomous animal accidents, among others.…”
Section: Discussionsupporting
confidence: 87%
“…The extreme clutter arising due to hoarding behavior impacts public health as it can lead to unsanitary community conditions and spread of diseases, particularly zoonoses [2,3]. These unsanitary conditions have an impact on the health of the individual with hoarding disorder and may lead to risks such as falling objects, fire hazards, and fire exit obstructions, which compromise their safety and welfare and lead to social vulnerability [4][5][6][7][8][9]. Other negative effects are primarily associated with poor physical health, increased risk of injury, exacerbation of chronic diseases, occupational impairment, and social concerns, such as homelessness, social isolation, and economic burden [4,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clutter may create significant safety risks that lead to eviction and homelessness (Nordsletten et al, 2014; Rodriguez et al, 2012; Schwartzman et al, 2017; Tolin, Frost, Steketee, Gray et al, 2008; Weiss & Khan, 2015). Hoarding is also associated with occupational impairment, difficulty carrying out activities of daily living (e.g., bathing), and difficulty performing routine household tasks (e.g., cooking) (Raeburn et al, 2015; Schwartzman et al, 2017). Hoarding symptoms can lead to financial problems due to disorganization (e.g., unable to keep track of bills) and/or excessive purchasing of unnecessary items (Tolin, Frost, Steketee, Fitch, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…the individual who is engaged in hoarding, close neighbours), and preventing evictions, which represent a special risk for low‐income residents with hoarding (Rodriguez et al, ). Community hoarding task forces and coalitions capitalise on the diversity of professional input and resources available to successfully address problems related to hoarding (Bratiotis, ; Gonzalez, Wu, & Baweja, ; Raeburn, Hungerford, Escott, & Clearly, ). Interventions involve professionals in an enforcement role, coming from fire prevention, law enforcement, or building inspection and maintenance, as well as those in a supportive role, such as mental health nurses or social workers (Bratiotis et al, ).…”
Section: Introductionmentioning
confidence: 99%